Cancer-associated pyroptosis: A new license to kill tumor - Kong, Qing; Zhang, Zhibin (Frontiers in Immunology, 2023)
Pyroptosis is a programmed necrotic cell death mediated by pore-forming Gasdermin (GSDM) proteins. After being unleashed from the C-terminal auto-inhibitory domains by proteolytic cleavage, the N-terminal domains of GSDMs oligomerize and perforate on the plasma membrane to induce cytolytic pyroptosis, releasing immune mediators and alarming the immune system. Upon infection or danger signal perception, GSDMD that functions downstream of the inflammasome, a supramolecular complex for inflammatory caspase activation, is cleaved and activated by inflammasome-activated caspase-1/4/5/11 in immune cells and epithelial cells to trigger pyroptosis and exert anti-infection protection. Unlike this inflammasome-activated pyroptosis (IAP), recent studies also suggest an emerging role of cancer-associated pyroptosis (CAP), mediated by other GSDMs in cancer cells, in provoking anti-tumor immunity. IAP and CAP share common features like cell membrane rupture but also differ in occurrence sites, activating mechanisms, secreting cytokines and biological outcomes. Here we review the most recent knowledge of cancer-associated pyroptosis and present a promising avenue for developing therapeutic interventions to enhance anti-tumor immunity for cancer prevention and treatment.